MEDIA PITA PLASTIK UNTUK MENINGKATKAN HASIL BELAJAR LOMPAT TINGGI - Rossfi Nanang Hidayat; Muhamad Salabi; Sukarman (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to improve students' learning outcomes in the scissors-style high jump through plastic tape media at SDN 2 Kayangan. The research employed classroom action research conducted in two cycles, each consisting of planning, action, observation, and reflection. The subjects were 20 fifth-grade students, consisting of 10 boys and 10 girls. Data were collected using observation sheets, scissors-style high jump performance tests, cognitive assessment, and documentation. The results showed a progressive improvement in students' achievement. In the pre-cycle, the class mean score was 68.91, with only 5 students (25%) achieving the minimum mastery criterion. In Cycle I, the mean score increased to 73.75, with 16 students (80%) achieving mastery. In Cycle II, the mean score reached 84.69, with all 20 students (100%) achieving mastery. These findings indicate that plastic tape media can make high jump learning safer, more visual, and more confidence-building for elementary school students. In conclusion, plastic tape media effectively improved scissors-style high jump learning outcomes among fifth-grade students at SDN 2 Kayangan.